Sweet foods dietary pattern enhances negative associations of perceived indoor air quality during pregnancy with postpartum depression. (18th November 2022) - Hu, Jiajin; Liu, Yilin; Ma, Yanan; Gao, Ming; Wan, Ningyu; Li, Lin; Liu, Borui; Wen, Deliang
Abstract: Postpartum depression (PPD) is possibly caused by indoor air pollution and may be modified by maternal diet during pregnancy. Using the data from a prospective cohort study, we examined the interaction between indoor air quality and maternal dietary patterns on PPD development. A perceived indoor air quality (PIAQ) score was used to assess indoor air pollution. A higher PIAQ score indicated a worse indoor air quality. Women with higher PIAQ scores were at increased risk for PPD (tertile 3 vs. tertile 1, odds ratio [OR] = 2.12, 95% confidence interval [CI] = 1.37–3.29). Compared with a lower adherence to a "sweet foods pattern" (OR = 1.20, 95% CI = 0.66–2.18), a higher adherence to a "sweet foods pattern" enhanced the hazardous associations of the PIAQ on PPD (OR = 3.09, 95% CI = 1.81–5.27, adjusted p for interaction = 0.044). Higher adherence to a "whole grain‐seafood pattern" and lower adherence to a "traditional pattern" also increased the risk for PPD, although the p values for the interaction were not significant. Our findings provide further evidence of the link between diet during pregnancy, air pollution, and PPD, and it can be used to develop PPD prevention strategies.